Penerapan Pembelajaran Penemuan Dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Sekolah Dasar - Jayanti Putri Purwaningrum (Universitas Muria Kudus, 2018)
This study aims to: (1) find out the test result average of the students mathematic problem solving ability which uses the discovery- learning assisted by manipulative demonstrative tools is above KKM; (2) find out the students mathematic problem solving ability which uses the discovery- learning assisted by manipulative demonstrative tools reaches 75% of classical completeness ; and (3) find out the increase of the students mathematic problem solving ability through the discovery- learning assisted by manipulative demonstrative tools. This study is an experimental research through the discovery-learning assisted by manipulative demonstrative tools with one group pretest posttest technique. Instrument used in this research is the mathematic problem solving ability test, students attitude scale questionnaire, learning device and observation sheet. Based on data analysis has been conducted, it is obtained conclusions that: (1) the test result average of the students mathematic problem solving ability which uses the discovery- learning assisted by manipulative demonstrative tools is under KKM; (2) the students mathematic problem solving ability which uses the discovery- learning assisted by manipulative demonstrative tools doesn’t reach 75% of classical completeness; (3) the discovery- learning assisted by manipulative demonstrative tools can increase the students mathematic problem solving ability.